Antiferroelectrics: Multilayer Lead‐Free Ceramic Capacitors with Ultrahigh Energy Density and Efficiency (Adv. Mater. 32/2018). Issue 32 (6th August 2018) - Li, Jinglei; Li, Fei; Xu, Zhuo; Zhang, Shujun
Abstract : Antiferroelectric materials used for energy‐storage devices show the advantage of high power density but have low efficiency and inferior cycling reliability. In article number1802155, Fei Li, Shujun Zhang, and co‐workers develop lead‐free relaxor antiferroelectrics possessing high energy density and efficiency with good cycling reliability and thermal stability, by introducing a relaxor component, which interrupts the long‐range ordering of the antiferroelectrics.